Microbe-assisted fabrication of circularly polarized luminescent bacterial cellulosic hybrids - Yongjie Sun; Dan Zhang; Zhiqiang Dong; Jinxiao Lyu; Chunfei Wang; Jun Gong; Koon Ho Wong; Changfeng Wu; Xuanjun Zhang (Nature Communications)
Abstract The fabrications of circularly polarized luminescent (CPL) material are mainly based on the chemical and physical strategies. Controlled biosynthesis of CPL-active materials is beset with difficulties due to the lack of bioactive luminescent precursors and bio-reactors. Enlighted by microbe-assisted asymmetric biosynthesis, herein, we show the in situ bacterial fermentation of Komagataeibacter sucrofermentants to fabricate a series of bacterial cellulosic biofilms with CPL of green, orange, red, and near-infrared colors. This process can trigger CPL emission for CPL-silent glycosylated luminophores and amplify the glum of weak CPL-active luminophores up to a 10−2 scale. To confirm glycosidic bonds formation during the bacterial copolymerization process, we develop an assay utilizing the cellulase-catalyzed biodegradation of BC hybrids. More importantly, we achieve the information encryption and Fe3+ dual-channel detection based on hybrid bacterial cellulosic biofilms. Therefore, this study not only provides another vision for CPL materials preparation but also broadens the application of bacterial cellulosic hybrids.